influence of availability of ventilation in work / study spaces on quality of work / study - Аскольченко, М. В. (БНТУ, 2020)
This article reflects the importance of having a ventilation system in work / school premises, shows its effect on the work process, and describes how to create ventilation in the absence of professional equipment manufactured for air exchange.